1995
DOI: 10.1086/467965
|View full text |Cite
|
Sign up to set email alerts
|

Medical Malpractice Insurance in the Wake of Liability Reform

Abstract: This article examines the effect of the liability reforms on medical malpractice insurance over the 1984-91 period. This is the first study to use data by firm and by state for every firm writing medical malpractice insurance over that time period. The liability reforms increased insurance profitability (that is, decreased the loss ratios), where the main mechanism of influence was through decreasing losses. The quantile regression estimates imply that the greatest effects of liability reform are on the most u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…This study extends our previous work reported in Viscusi and Born (1995) in which we focus primarily on the case studies of the medical malpractice reforms in Michigan and…”
Section: An Overview Of Tort Liability Reformssupporting
confidence: 77%
See 1 more Smart Citation
“…This study extends our previous work reported in Viscusi and Born (1995) in which we focus primarily on the case studies of the medical malpractice reforms in Michigan and…”
Section: An Overview Of Tort Liability Reformssupporting
confidence: 77%
“…Our past analysis of the 1970s reforms in Viscusi and Born (1995) indicated that there was no long-term influence of these reform efforts on the current performance of the liability system.…”
Section: An Overview Of Tort Liability Reformsmentioning
confidence: 99%
“…Again, they found that malpractice reforms had an inconsistent impact on malpractice insurance premiums. The only reforms which significantly lowered premiums were those which limited the size of awards or those which limited the statute of limitations (Viscusi and Born, 1995, had similar findings with respect to malpractice premiums). None of the malpractice reforms were found to decrease frequency.…”
Section: Medical Malpractice Reformmentioning
confidence: 84%
“…In contrast to Danzon, Sloan (1985) estimated the impact that various factors, including malpractice reforms, had upon malpractice insurance premiums (see also Viscusi and Born, 1995). Malpractice insurance premiums reflect, albeit imperfectly, increased malpractice frequency and severity through increased average benefits paid by insurers.…”
Section: Medical Malpractice Reformmentioning
confidence: 99%
“…14 Sloan, 1985;Danzon et al, 2004;Viscusi and Born, 1995;Viscusi and Born, 2005: no longer have records.…”
Section: A Overview Of Primary Study Resultsmentioning
confidence: 99%